Eye Diseases Classification using Back Propagation with Parabola Learning Rate - Shrooq R. Hameed; Hanaa M. Ahmed (Al-Qadisiyah Journal of Pure Science, 2020)
Human eye disease classification adapted by many pieces of research in the last decade due to the importance of eye organ for humans and the evolution in classification techniques. Seven external eye diseases plus normal eye classified in this paper using backpropagation with linear cyclic learning rate-based parabola function. The classification accuracy achieved in this paper is (89.83%).